28.1.128 problem 151

Internal problem ID [4434]
Book : Differential equations for engineers by Wei-Chau XIE, Cambridge Press 2010
Section : Chapter 2. First-Order and Simple Higher-Order Differential Equations. Page 78
Problem number : 151
Date solved : Monday, January 27, 2025 at 09:17:17 AM
CAS classification : [[_homogeneous, `class C`], _dAlembert]

\begin{align*} 2 {y^{\prime }}^{3}-3 {y^{\prime }}^{2}+x&=y \end{align*}

Solution by Maple

Time used: 0.049 (sec). Leaf size: 53

dsolve(2*diff(y(x),x)^3-3*diff(y(x),x)^2+x=y(x),y(x), singsol=all)
 
\begin{align*} y \left (x \right ) &= x -1 \\ y \left (x \right ) &= \frac {\left (-2 x +2 c_{1} \right ) \sqrt {3 x -3 c_{1}}}{9}+c_{1} \\ y \left (x \right ) &= \frac {\left (2 x -2 c_{1} \right ) \sqrt {3 x -3 c_{1}}}{9}+c_{1} \\ \end{align*}

Solution by Mathematica

Time used: 0.000 (sec). Leaf size: 0

DSolve[2*D[y[x],x]^3-3*D[y[x],x]^2+x==y[x],y[x],x,IncludeSingularSolutions -> True]
 

Timed out